Case report: Ethylene glycol intoxication presenting as a mimic of acute stroke: a report of three cases - Héja, Máté; Oláh, László (Frontiers in Stroke, 2023)
Stroke is a major cause of death and disability presenting with acute focal neurological symptoms of vascular origin. Several other disorders may cause symptoms similar to a stroke, referred as stroke mimics. Misdiagnosis of stroke mimics may lead to potentially harmful treatments, including thrombolysis. Intoxication is a rare, but possible cause of stroke mimic. We present three cases of ethylene glycol poisoning presenting as acute stroke mimic within the time window of thrombolytic therapy. Two of three patients (54-year-old, male) had dysarthria, nystagmus and truncal ataxia on admission. The third patient with a history of chronic alcoholism was presented after an epileptic seizure with mixed aphasia and confusion. NCCT and CTA were negative in all 3 cases. As stroke could not be excluded in any of the patients, thrombolysis was performed. Some hours later agitation, somnolence and hyperventilation developed in 2 of 3 patients. One patient's consciousness deteriorated rapidly, he became comatose and tetraplegic. Blood gas analysis showed acidosis in 2 of 3 patients, and toxicological screening revealed ethylene-glycol intoxication in all 3 cases. Due to the appropriate treatment, 2 of 3 patients became symptom-free, however, one of the 3 patients died. Our cases show that ethylene glycol intoxication in its early phase may mimic acute stroke resulting in an unnecessary thrombolytic therapy. Symptoms not characteristic of a stroke, such as hyperventilation, agitation, and disturbance of consciousness, may appear later and warn of intoxication. The final diagnosis of ethylene-glycol intoxication can be established by a severe metabolic acidosis and toxicological screening. Close monitoring of symptoms might contribute to early recognition of ethylene-glycol intoxication and its effective treatment.